Development of a face-to-face injunctive norms brief motivational intervention for college drinkers and preliminary outcomes - Prince, Mark A. (Psychol Addict Behav, 2015)
Findings are presented from the first randomized clinical trial that compared changes in alcohol consumption and alcohol-related consequences among college student drinkers from baseline to follow-up across four conditions: (a) a new single component injunctive norms brief motivational intervention (IN-BMI) condition, (b) a single component descriptive norms brief motivational intervention (DN-BMI), (c) a Combined IN and DN brief motivational intervention (Combined-BMI), and (d) assessment-only control. DN-BMI focused on the juxtaposition of personal, perceived, and actual alcohol use by typical same-sex students at your university. INBMI focused on the juxtaposition of personal, perceived, and actual attitudes about alcohol related consequences by the typical same-sex student at your university. Exploratory analyses assessed the effect of IN-BMI and DN-BMI on matched (e.g., the effect of DN-BMI on perceived DN) and mismatched norms (e.g., the effect of DN-BMI on perceived IN). IN-BMI resulted in greater decreases in alcohol use and consequences when delivered alone and in conjunction with DN-BMI compared to the control condition. Further, the Combined-BMI condition reported greater reductions in alcohol use but not consequences compared to the DN condition. Receiving IN-BMI either alone or in combination with DN-BMI produced greater changes in IN perceptions than were produced in the control group. Grounded in norms theory, this study examined how college student problem drinking is affected by both IN-BMI and DN-BMI alone and in combination. We conclude that IN-BMI alone or in combination with DN-BMI is able to modify alcohol use and reduce alcohol related consequences.